The Relationship Of Social Support With Self Compassion In Adolescents With Divorced Parents - Miasari, Lita; Aulia, Prima (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The title of this research is The relationship between social support and self-compassion in teenagers with divorced parents. Aims of this research is to known the relationship between┬á those variables. The design of this research is correlational quantitative method. In this study the subjects were teenagers with divorced parents, aged 13-22 years old, and domiciled in the city of Padang, West Sumatra. This research uses incidental sampling technique. From the product moment correlation test of the two variables, the results of the significance value are obtained p= .005 (p<.05)and r = .381. Social support own a positive relationship with self compassion. Which is to say if a person gets high social support, that person will have high self compassion as well, where social support own a positive relationship with self compassion. It implies that social support contributes 14.5% to self compassion.Keywords: Social support, self compassion, adolescents, divorced parents